Latin American consensus on hypertension in patients with diabetes type 2 and metabolic syndrome - López Jaramillo, Patricio (2012)
The present document has been prepared by a group of experts, members of cardiology, endocrinology and diabetes societies of Latin American countries, to serve as a guide to physicians taking care of patients with diabetes, hypertension and comorbidities or complications of both conditions. Although the concept of 'metabolic syndrome' is currently disputed, the higher prevalence in Latin America of that cluster of metabolic alterations has suggested that 'metabolic syndrome' is a useful nosographic entity in the context of Latin American medicine. Therefore, in the present document, particular attention is paid to this syndrome in order to alert physicians on a particularly high-risk population, usually underestimated and undertreated. These recommendations result from presentations and debates by discussion panels during a 2-day conference held in Bucaramanga, in October 2012, and all the participants have approved the final conclusions. The authors acknowledge that the publication and diffusion of guidelines do not suffice to achieve the recommended changes in diagnostic or therapeutic strategies, and plan suitable interventions overcoming knowledge, attitude and behavioural barriers, preventing both physicians and patients from effectively adhering to guideline recommendations.